2019
DOI: 10.1038/s41598-019-50779-9
|View full text |Cite
|
Sign up to set email alerts
|

Strain diversity of Treponema pallidum subsp. pertenue suggests rare interspecies transmission in African nonhuman primates

Abstract: In our most recent study, we found that in Tanzania infection with Treponema pallidum (TP) subsp. pertenue (TPE) is present in four different monkey species. In order to gain information on the diversity and epidemiological spread of the infection in Tanzanian nonhuman primates (NHP), we identified two suitable candidate genes for multi-locus sequence typing (MLST). We demonstrate the functionality of the MLST system in invasively and non-invasively collected samples. While we were not able to demonstrate freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 33 publications
8
38
2
Order By: Relevance
“…Notably, in all TPE strains sampled from this ecosystem, there is no indication that strains were epidemiologically linked, as no identical genomes were sampled. In contrast, in other species in different ecosystems, nearly identical genomes were observed, potentially indicative of an epidemiological link: particularly the two green monkey populations in Bijilo In agreement with a recent study of TPE strain diversity among NHPs from Tanzania using multi-locus sequence typing [52], simian derived isolates included in our analyses did not form monophyletic clades based on host species or the type of symptoms caused by an isolate, but rather clustered based on geography. Three geographical clades were prominent; the east African clade consisting of isolates from Tanzania and the two West African sister clades that formed well-supported monophyletic groups.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, in all TPE strains sampled from this ecosystem, there is no indication that strains were epidemiologically linked, as no identical genomes were sampled. In contrast, in other species in different ecosystems, nearly identical genomes were observed, potentially indicative of an epidemiological link: particularly the two green monkey populations in Bijilo In agreement with a recent study of TPE strain diversity among NHPs from Tanzania using multi-locus sequence typing [52], simian derived isolates included in our analyses did not form monophyletic clades based on host species or the type of symptoms caused by an isolate, but rather clustered based on geography. Three geographical clades were prominent; the east African clade consisting of isolates from Tanzania and the two West African sister clades that formed well-supported monophyletic groups.…”
Section: Discussionsupporting
confidence: 89%
“…This study links yaws-like pathology to the actual detection of TPE in a wild chimpanzee, providing evidence that at least part of the suggestive lesions often observed in wild great apes are caused by this pathogen. These data join a growing body of evidence demonstrating that many NHP species across sub-Saharan Africa are infected with TPE (1,9). This finding could potentially be problematic for the ongoing campaign to eradicate TPE globally by 2030 (13), although, clearly, data from TPE-infected humans in this region are needed to determine whether zoonotic transmission of this pathogen occurs.…”
Section: Discussionmentioning
confidence: 55%
“…The lesions observed in these images closely resembled those of the wild female from the Sangaredi region described in this article, including shrunken eyes, deformation of the face, absence of the nose, and hypertrophied and depigmented lips (in 1 case, the lips were completely missing; Figure 1, panels B, C). Molecular investigations of the pathogen(s) causing these infections is clearly warranted, perhaps through noninvasive screening of TPE in feces, bones, or primate-associated flies (9,12).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…pertenue , the Serengeti National Park and Fribourg‐Blanc strains were more basal to the human T. pallidum subspecies strains (Harper et al, ). In a survey of 85 individuals from six primate species, Chuma et al () analyzed two genes ( tp0548 and tp0448 ) and showed that strains, all classed as T. pallidum subsp. pertenue despite differing clinical phenotypes, appear to cluster based on geography rather than host species, which suggests that there has been transmission among primate species.…”
Section: Epidemiological and Genetic Researchmentioning
confidence: 99%